Formulation of Criminal Law Calculation Regarding Insufficient Compensation Money in Corruption Cases - Sofyansyah, Ade; Sujadmiko, Bayu (Faculty of Law, Universitas Lampung, 2023)
So far, corrupt convicts continue serving full sentences even though they have paid part of the replacement money. At the same time, there is no specific formulation regarding calculating the amount of compensation paid for the length of imprisonment for replacement money that needs to be paid more. This is certainly a problem for the prosecutor's office as law enforcement officers in Indonesia to eradicate corruption cases. So that a special formulation is needed in calculating the replacement money, which is then ratified in legal regulation; based on these legal issues, this research aims to examine the perspective of the formulation of criminal law calculations on insufficient replacement of money in corruption cases. This research uses a normative research methodology and examines written law from various perspectives, including theory, history, philosophy, comparison, structure and composition, scope and material, consistency, general explanation and article by article, formality, and binding power of a law-law. This research includes primary, secondary, and tertiary legal materials as data sources. Data processing includes data verification, data marking, data reconstruction, and data systematization. Furthermore, a qualitative descriptive analysis was carried out on the data. The study results indicate that the calculation of the criminal law on insufficient replacement money in corruption cases is based on a proportionality or comparability approach.